2021
DOI: 10.1002/jcph.1969
|View full text |Cite
|
Sign up to set email alerts
|

Whether Immunostimulants Are Effective in Susceptible Children Suffering From Recurrent Respiratory Tract Infections: A Modeling Analysis Based on Literature Aggregate Data

Abstract: Immunostimulants are gradually being used in the prevention and treatment of recurrent respiratory tract infections in susceptible children, but their drug effects have not been quantified. The purpose of this study was to confirm the efficacy of immunostimulants in the prevention and treatment of recurrent respiratory tract infections in susceptible children. A model‐based meta‐analysis was used to describe the time course of placebo and immunostimulants in the prevention of respiratory tract infections in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Most recently, Zhang and colleagues 25 published a systematic review assessing whether immunostimulants are effective in susceptible children suffering from recurrent RTI, using a modeling analysis based on literature aggregate data by constructing a quantitative pharmacodynamic model. The factors potentially affecting the slope of the cumulative number of RTIs were explored by covariate modeling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Zhang and colleagues 25 published a systematic review assessing whether immunostimulants are effective in susceptible children suffering from recurrent RTI, using a modeling analysis based on literature aggregate data by constructing a quantitative pharmacodynamic model. The factors potentially affecting the slope of the cumulative number of RTIs were explored by covariate modeling.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Zhang et al 25 constructed a quantitatively pharmacodynamic regression model using aggregated data from literature and found that the OM-85 BV could reduce the incidence of RTIs by 0.21 times per month; that is, ~1.26 fewer RTIs every half-year. Among these seven systematic review on RTIs, only one review 22 had "high confidence" (i.e., ≤1 non-critical weakness, providing an accurate and comprehensive summary of the results of the available studies that address the question of interest), and six [19][20][21][23][24][25] "critical low confidence" (i.e., >1 critical flaw and should not be relied on to provide an accurate and comprehensive summary of existing studies).…”
Section: Discussionmentioning
confidence: 99%
“…Orally administered OM-85, absorbed through the gastrointestinal tract, is an effective stimulant that activates the innate and adaptive arms of the immune system, and leads to functional immune responses against the invading pathogens. Since the 1950s, OM-85 has been widely used for the prevention of recurrent respiratory tract infections in several European and Asian countries ( 47 - 49 ). Respiratory tract infection is a major predisposing factor that contributes to asthma exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…The perspective of “new-age” immunotherapy, such as checkpoint inhibition triggering the immunopathology events or cytokine therapies modulating inflammation development, has been raised to reduce the burden of infectious diseases threatened by antibiotic resistance ( 46 ). The recent meta-analysis has shown that the immunostimulants, OM-85 BV and pidotimod, which have been widely used and suggested by pediatricians in the prevention and treatment of RRTi in susceptible children, can reduce the incidence of respiratory tract infections by 0.21 and 0.19 per month, respectively ( 47 ); however, long-term use of the said drugs is challenging for children and their families. Actually, probiotics do have great potential as the “new-age” immunotherapy, as several in vitro / in vivo studies have summarized the strain-specific immunomodulatory effects and the stimulation of interferon (IFN) pathways to antagonize viral respiratory infections due to that microbiome has co-evolved with the eukaryotic genome of its host ( 26 , 48 ).…”
Section: Discussionmentioning
confidence: 99%